1994
DOI: 10.1210/endo.134.3.7509733
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of nitric oxide synthase (NOS) gene expression together with NOS activity in the rat hypothalamo-hypophysial system after chronic salt loading: evidence of a neuromodulatory role of nitric oxide in arginine vasopressin and oxytocin secretion.

Abstract: Chronic salt loading up-regulated the expression of neuronal nitric oxide synthase (NOS) mRNA in the supraoptic nucleus (SON) and paraventricular nucleus (PVN) of the hypothalamus with a concomitant increase in NOS activity in the posterior pituitary. Once daily ip injection of N-omega-nitroarginine (N-Arg), a NOS inhibitor, significantly inhibited NOS activity in the posterior pituitary in a dose-dependent manner, but did not influence NOS mRNA levels. Two percent salt loading for 3 or 4 days significantly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(78 citation statements)
references
References 36 publications
4
73
0
1
Order By: Relevance
“…The NADPH-diaphorase (NADPH-d) enzyme activity that is associated with NOS activity sustains routine fixation procedures with aldehydes and has been used as a reliable indicator of NOS enzymatic activity in paraformaldehyde-fixed brain tissue including the SON (Kadowaki et al, 1994;Matsumoto et al, 1993;Villar et al, 1994). In agreement with others, we found that hyperosmotic stimulation of early and late adulthood rats triggered an activitydependent increase in NADPH-d staining density in the SON (Soinila et al, 1999;Yun et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The NADPH-diaphorase (NADPH-d) enzyme activity that is associated with NOS activity sustains routine fixation procedures with aldehydes and has been used as a reliable indicator of NOS enzymatic activity in paraformaldehyde-fixed brain tissue including the SON (Kadowaki et al, 1994;Matsumoto et al, 1993;Villar et al, 1994). In agreement with others, we found that hyperosmotic stimulation of early and late adulthood rats triggered an activitydependent increase in NADPH-d staining density in the SON (Soinila et al, 1999;Yun et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…NO has been described as an activity-dependent modulator of the magnocellular neurosecretory system. We and others have shown that NO signaling is required for stimulated VP release from SON tissue punches (Gillard et al, 2007) and the latter serves to regulate MNC electrical activity and pituitary VP output (Kadowaki et al, 1994;Liu et al, 1998;Stern and Ludwig, 2001;Stern and Zhang, 2005). Moreover, nNOS expression and NOS activity (as assessed by NADPH-d) in MNCs appears to be responsive to physiological state, suggesting an activity-dependent role for NO signaling in the control of body water and salt balance.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Further research will be necessary to localize the NOergic neurons in higher brain centers that innervate the PI of Xenopus lae6is and to investigate the NOergic input of the PI via fibers running through the median eminence. These fibers may appear similar to the NOergic nerve endings found in the mammalian PN (Kadowaki et al, 1994;Pow, 1994;Vanhatalo and Soinila, 1995), although due attention should be paid to the difference in pituitary innervation between mammals and amphibians. Also in analogy with the mammalian pituitary, a local (paracrine or autocrine) effect of NO in the PN (Pow, 1994) and the PI ( Vanhatalo and Soinila, 1995) cannot be excluded, but requires further studies.…”
Section: Possible Sources Of Nos In the Pimentioning
confidence: 63%
“…It was reported that NOS mRNA and NADPH-d activity are upregulated in response to salt loading [17,38,39] or hypotension [40]. Stimulatory action was augmented by inhibitors of NO formation, suggesting that endogenous NO has an inhibitory effect on the release of these peptides [30,34,35].…”
Section: Posterior Pituitarymentioning
confidence: 99%